EMERGING ISSUES IN EDUCATIONAL MEASUREMENT: AUTHENTIC ASSESSMENT - Abubakar Ukashatu (lppm Universitas Negeri Jakarta, 2021)
Authentic assessment is a tool of evaluating students learning applicable to real world situation. It is unavoidable tools for modern assessment of learning outcomes. It can be apply as formative or summative assessments or for both assessment types. This paper attempted to examined the concept of assessment and its types, the concept of authentic assessment and its categories, the forms of authentic assessment, the tools used for authentic assessment, methods used in authentic assessment, steps involved in authentic assessment, advantages of authentic assessment, challenges of authentic assessment among others. The paper concludes that it is a high time for authentic assessment to replace traditional methods of assessment in all level of learning. The paper also recommended that the Curriculum Planners should design a curriculum based on types of authentic assessment for all levels of learning, the application of authentic assessment at all levels of learning, time has comes to move from traditional method of assessment to authentic assessment form and required competencies must be possessed by the teacher in order to carry out authentic assessments through proper training.